2006
DOI: 10.2460/ajvr.67.5.858
|View full text |Cite
|
Sign up to set email alerts
|

Association between findings on palmarodorsal radiographic images and detection of a fracture in the proximal sesamoid bones of forelimbs obtained from cadavers of racing Thoroughbreds

Abstract: Biaxial fractures of proximal sesamoid bones were common in cadavers of racing Thoroughbreds. Differences between medial and lateral bones for characteristics associated with fracture may relate to differences in fracture pathogeneses for these bones. Osteophytes and vascular channels were common findings; however, fractures were less likely to occur in bones with these features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 14 publications
6
39
1
Order By: Relevance
“…9,11,12,14,15,[17][18][19] In only 1 Thoroughbred study 10 did metacarpal and carpal injuries exceed proximal sesamoid bone injuries. Palpation should be useful for detection of some distal scapular spine lesions 35 ; ultrasonography for scapular and ilial wing lesions 36,40,41 ; radiography for humeral, metacarpal and metatarsal, and tibial lesions 39,[42][43][44] ; and scintigraphy for scapular, humeral, metacarpal and metatarsal, pelvic, and tibial stress remodeling. 15,19,20,24,26,32,[34][35][36][37][38][39] Evidence of preexisting periosteal callus was noted in association with complete fractures of the scapula, humerus, and tibia for some Quarter Horses of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12,14,15,[17][18][19] In only 1 Thoroughbred study 10 did metacarpal and carpal injuries exceed proximal sesamoid bone injuries. Palpation should be useful for detection of some distal scapular spine lesions 35 ; ultrasonography for scapular and ilial wing lesions 36,40,41 ; radiography for humeral, metacarpal and metatarsal, and tibial lesions 39,[42][43][44] ; and scintigraphy for scapular, humeral, metacarpal and metatarsal, pelvic, and tibial stress remodeling. 15,19,20,24,26,32,[34][35][36][37][38][39] Evidence of preexisting periosteal callus was noted in association with complete fractures of the scapula, humerus, and tibia for some Quarter Horses of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of post mortem examination (Parkin et al 2004c;Anthenill et al 2006;Boden et al 2006) when attempting to identify risk factors for individual types of fracture was emphasised. Unpublished data (T. Parkin) from a study conducted in the UK between 1998 and 2005 identified significant differences in race day reports of fractures and later post mortem diagnoses.…”
Section: Case Definitionsmentioning
confidence: 99%
“…Results of necropsies performed in other studies indicate that biaxial (medial and lateral) PSB fracture is the most common cause for failure of the MCPJ for racehorses in California, 7,13 Kentucky, 2 Florida, 4,b,c and Hong Kong a and an uncommon cause for failure of the MCPJ for racehorses in the United Kingdom. 10,14,15 Histologic evaluation has identified structural changes in the PSBs of trained versus untrained Thoroughbreds.…”
mentioning
confidence: 97%